Foreign Trade Situation of Nepal - Shrestha , Shiva Sharan (PYC Nepal Journal of Management, 2016)
This study analyzes the growth, direction and trade balance of Nepal’s foreign trade for the period 2005/6 to 2014/15. The study finds that the import has grown rapidly (at an annual average rate of 17%) and the import at snail’s pace (at an annual rate of 4%) over the study period. As a result the trade balance is negative and growing every year. Such a trend can’t sustain for long. Further, Nepal’s foreign trade is too much dependent (exceeding two-third of both export and import) on India which needs to be diversified to rest of the world.